The functionality, bioavailability, and bioactive peptides in white cheeses produced in Turkey - Turan, Neslihan; Durak, Muhammed Zeki (SPRINGER, 2022)
The main objectives of this study were to determine antioxidant, angiotensin-converting enzyme-inhibitory (ACE-I), and antibacterial activities of traditional Turkish white cheeses. The bioactivities of the cheeses tested in the low-molecular-weight fractions of water-soluble extracts. The effect of in vitro digestion on the functional potential of white cheeses was also considered. The antioxidant activity of water-soluble extracts of white cheeses was tested with FRAP (Ferric Reducing Ability of Plasma) and ABTS [2,20-azinobis-(3-ethylbenzothiazoline-6-sulphonic acid)] assays. Cow cheese and goat cheese showed better antioxidant activities in the FRAP and ABTS assays, respectively. However, after in vitro digestion, goat cheese displayed higher radical scavenging activity than its counterparts. Goat cheese also exhibited better ACE-I activity, although ACE-I activity was inhibited by the in vitro digestion, probably due to the further proteolysis of ACE-I peptides. All samples showed an antibacterial effect on Salmonella typhimurium ATCC 14028 and Staphylococcus aureus ATCC 25923. The fractions were analyzed with orbitrap liquid chromatography-tandem mass spectrometry to determine the sequences of peptides. White cheeses contained 42 sequences previously reported as bioactive peptides with the functions of ACE-I, antioxidant, antimicrobial, inhibition of cholesterol solubility, osteoanabolic, and antidiabetic. White cheese is a rich source of bioactive peptides with various properties.
Keywords: Orbitrap; ACE-inhibitory; ABTS; FRAP; Antibacterial; WATER-SOLUBLE EXTRACTS; ANTIOXIDANT ACTIVITY; IN-VITRO; MILK; PROFILE; FOOD; PROTEOLYSIS; GENERATION; Food Science & Technology